Charaterization of mosquito larval habitats in Qatar - Fatima Abdulla Alkhayat (Saudi Journal of Biological Sciences, 2020)
Mosquito borne diseases have remained a grave threat to human health and are posing a significant burden on health authorities around the globe. The understanding and insight of mosquito breeding habitats features is crucial for their effective management. Comprehensive larval surveys were carried out at 14 sites in Qatar. A total of 443 aquatic habitats were examined, among these 130 were found positive with Culex pipiens, Cx. quinquefasciatus, Cx. mattinglyi, Ochlerotatus dorsalis, Oc. caspius and Anopheles stephensi. The majority of positive breeding habitats were recorded in urban areas (67.6%), followed by livestock (13.8%), and least were in agriculture (10.7%). An. stephensi larvae were positively correlated with Cx. pipien, Cx. quinquefasciatus, and negatively with water salinity. Large and shaded habitats were the most preferred by An. stephensi. In addition, Cx. pipiens was positively associated with the turbidity and pH, and was negatively associated with vegetation and habitat size. A negative association of Cx. quinquefasciatus with dissolved oxygen, water temperature, and salinity, while positive with habitat surface area was observed. Oc. dorsalis was negatively correlated with pH, water temperature, depth, and habitat surface area, whereas salinity water was more preferable site for females to lay their eggs. These results demonstrate that environmental factors play a significant role in preference of both anopheline and culicine for oviposition, while their effective management must be developed as the most viable tool to minimize mosquito borne diseases.